The Role of Social Media in Shaping Elementary Students’ Character: A Netnographic Study of Facebook, TikTok, and Instagram Interactions - Liana (Jurnal Pendidikan: Media, Strategi, dan Metode, 2026)
Social media has become an influential digital environment where elementary students encounter values, behaviors, peer responses, and models of self-expression. Although social media is often discussed in relation to risk, distraction, and screen exposure, it can also become a character-learning space when students interact with educational content, community-service posts, creative projects, and supportive peer communication. This study explores the role of social media in shaping elementary students’ character through a netnographic analysis of Facebook, TikTok, and Instagram interactions. The study focused on ten character dimensions: responsibility, respect, honesty, discipline, empathy, cooperation, self-confidence, digital citizenship, tolerance, and creativity. Data were collected through simulated netnographic observation over a three-month period by examining platform-based content, student comments, peer interactions, responses to educational content, responses to viral trends, and digital citizenship practices. The data were analyzed using thematic analysis. The findings revealed seven major themes: social media as a character-learning space, peer influence and character formation, digital empathy and online support, creativity and self-expression, risks of social comparison, digital citizenship challenges, and educational content as a positive influence. Facebook interactions were most strongly associated with empathy, cooperation, and social responsibility; TikTok stimulated creativity, curiosity, and initiative but also exposed students to peer pressure and risky imitation; Instagram encouraged creativity, appreciation, tolerance, confidence, and project sharing but also produced signs of unhealthy social comparison. The study concludes that social media plays a dual role in shaping elementary students’ character. It can strengthen positive values when guided by educational content and supportive interaction, but it can also weaken empathy, critical judgment, and self-esteem when students are exposed to inappropriate comments, risky trends, and idealized influencer culture. Therefore, schools and parents need to strengthen digital citizenship education, guided media literacy, ethical online communication, and reflective social media use among elementary students.